Une liste de mercenaires trouvée à Scotoussa (Thessalie) - Decourt, Jean-Claude; Tziafalias, Athanasios (Tekmeria, 2011)
This paper publishes a fragmentary inscription discovered a few years ago in the territory of the ancient city of Scotoussa in Thessaly. The text, dating to the 3rd century BC, lists the names of a small number of mercenaries, horsemen and infantrymen, recruited from several cities or peoples of Thessaly and nearby regions. The authors discuss the role of this contingent in the defense of the territory of Scotoussa, of which they offer a brief picture.